Planning for Implementation Success Using RE-AIM and CFIR Frameworks: A Qualitative Study - King, Diane K.; Shoup, Jo Ann; Raebel, Marsha A.; Anderson, Courtney B.; Wagner, Nicole M.; Ritzwoller, Debra P.; Bender, Bruce G. (Frontiers in Public Health, 2020)
Background: RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) and CFIR (Consolidated Framework for Implementation Research) dissemination and implementation frameworks define theory-based domains associated with the adoption, implementation and maintenance of evidence-based interventions. Used together, the two frameworks identify metrics for evaluating implementation success, i.e., high reach and effectiveness resulting in sustained practice change (RE-AIM), and modifiable factors that explain and enhance implementation outcomes (CFIR). We applied both frameworks to study the implementation planning process for a technology-delivered asthma care intervention called Breathewell within an integrated care organization. The goal of the Breathewell intervention is to increase the efficiency of delivering resource-intensive asthma care services. Methods: We reviewed historical documents (i.e., meeting agendas; minutes) from 14 months of planning to evaluate alignment of implementation team priorities with RE-AIM domains. Key content was extracted and analyzed on topics, frequency and amount of discussion within each RE-AIM domain. Implementation team members were interviewed using questions adapted from the CFIR Interview Guide Tool to focus their reflection on the process and contextual factors considered during pre-implementation planning. Documents and transcripts were initially coded using RE-AIM domain definitions, and recoded using CFIR constructs, with intent to help explain how team decisions and actions can contribute to adoption, implementation and maintenance outcomes. Results: Qualitative analysis of team documents and interviews demonstrated strong alignment with the RE-AIM domains: Reach, Effectiveness, and Implementation; and with the CFIR constructs: formal inclusion of provider and staff stakeholders in implementation planning, compatibility of the intervention with workflows and systems, and alignment of the intervention with organizational culture. Focus on these factors likely contributed to RE-AIM outcomes of high implementation fidelity. However, team members expressed low confidence that Breathewell would be adopted and maintained post-trial. A potential explanation was weak alignment with several CFIR constructs, including tension for change, relative priority, and leadership engagement that contribute to organizational receptivity and motivation to sustain change. Conclusions: While RE-AIM provides a practical framework for planning and evaluating practice change interventions to assure their external validity, CFIR explains why implementation succeeded or failed, and when used proactively, identifies relevant modifiable factors that can promote or undermine adoption, implementation, and maintenance.